Incision and drainage versus ultrasound guided needle aspiration in the management of lactational breast abscess. - Aisha Masroor Bhatti; Iqbal Memon, Amir; Naz, Tarnum; Latif, Sidra; Usman, Sualeha; Gul , Aisha (International Journal of Endorsing Health Science Research, 2021)
Background: Lactational breast abscess is attributed to higher morbidities among women, specifically from developing countries. Though many treatment options are available, still consensus regarding the modality yielding the best outcome is scarce. The study's objective was to compare the outcome of lactational breast abscess following incision & drainage (ID) versus ultrasound-guided needle aspiration (USGNA). Methodology: This prospective comparative investigation was carried upon a sample of 59 female patients with lactational breast abscess (chosen via non-probability, consecutive sampling), presenting to the Department of Surgery at Liaquat University Hospital, Hyderabad. The patients were divided into two groups, namely Group A (ID) and Group B (USGNA). Data was documented using a structured questionnaire, including inquiries related to sociodemographic details, disease specifics, and treatment outcomes (mainly abscess resolution, uninterrupted breastfeeding and fistula formation). Results: The results showed that 3 patients (5.08%) from group A developed mammary fistula, 26 (44.06%) with complete resolution, and only 1 (1.69%) patient attained uninterrupted breastfeeding. In group B, there was full resolution in 28 (47.45%) patients, and the abscess of 2 (3.38%) patients did not completely resolve, while 28 (47.45%) attained uninterrupted breastfeeding. Conclusion: It can be concluded that USGNA yields a better outcome in the treatment of lactational breast abscess in terms of lesser incidence of fistula development, the better probability of complete resolution and a significantly higher rate of attainments of the ability to breastfeed uninterruptedly.